Syndromic microphthalmia-3 caused by a mutation on gene SOX2 in a Colombian male patient (2016)
Syndromic microphthalmia-3 is a rare congenital syndrome associated with brain anomalies, esophageal atresia and genital anomalies. This is the case of a 4-year-old male with bilateral microphthalmia, short stature, neurodevelopmental delay, genital anomalies, and maternal exposition to glyphosate during pregnancy. Genetic testing detected a previously reported pathogenic heterozygous mutation in the SOX2 gene, confirming a diagnosis of syndromic microphthalmia-3. Whenever a patient presents bilateral microphthalmia, it is necessary to determine whether it is isolated or syndromic; afterwards, genetic testing should be performed in order to offer an effective genetic counseling.